THE INFLUENCE OF EMPLOYEE COMPETENCE, TRAINING, AND LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE THROUGH WORK MOTIVATION AT THE BPSDM OF SOUTH SULAWESI PROVINCE - Abrianty Antartika; Chablullah Wibisono; Nolla Puspita Dewi (CV. Radja Publika, 2026)
This study aims to analyze the influence of employee competence, training, and leadership style on employee performance through work motivation at the Human Resource Development Agency (BPSDM) of South Sulawesi Province. Employee performance is an important factor in supporting organizational effectiveness; therefore, it is necessary to identify factors that can improve performance. This research design uses a quantitative approach with a causal-comparative research type. The population in this study consisted of all Civil Servants (PNS) working at BPSDM of South Sulawesi Province, totaling 130 employees. This study applied a census method by involving all members of the population as research respondents. The data analysis technique used in this study was Partial Least Squares (PLS) to examine the relationships among variables in the research model. The results of the study indicate that employee competence has a positive and significant effect on employee performance, meaning that the higher the competence possessed by employees, the better the performance produced. Training is also proven to have a positive and significant effect on employee performance, indicating that effective training can improve employees' abilities and work productivity. In addition, leadership style has a positive and significant effect on employee performance, indicating that good leadership can encourage improved employee performance through clear direction, support, and effective communication.